Phonology of Molla Yâr Muhammed Nemengâni and Tuhfetü-l Abidin - Barlas, Hairatullah (Indonesian Journal of Innovation Studies, 2022)
As a master degree graduate thesis, we selected the Tuhfetüʾl-ʾÂbidîn. It is a collection of the poems written by Molla Yur Muhammed Nemengânî who was born in the 19th century in Nemengân. There are many poems from different poets in the book which consisting of 188 pages, but 108 pages belongs to our poet Nemengânî and this study focused on these pages. in the poems, poet was known by his surname, Muhlis. The text was found in Hoyham village in Badakhshan province, which is located on the borders of Afghanistan. The texts of the book have been transcribed and translated into Latin alphabets. Considering language characteristics, writing characteristics, phonetic features and shape characteristics, the texts were studied.